2017
DOI: 10.1007/s00253-017-8264-y
|View full text |Cite
|
Sign up to set email alerts
|

Microbial response to environmental stresses: from fundamental mechanisms to practical applications

Abstract: Environmental stresses are usually active during the process of microbial fermentation and have significant influence on microbial physiology. Microorganisms have developed a series of strategies to resist environmental stresses. For instance, they maintain the integrity and fluidity of cell membranes by modulating their structure and composition, and the permeability and activities of transporters are adjusted to control nutrient transport and ion exchange. Certain transcription factors are activated to enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(74 citation statements)
references
References 164 publications
0
74
0
Order By: Relevance
“…To protect cells from the damage caused by ROS, microorganisms have developed a variety of defense mechanisms against oxidative stress (Guan et al, ). Enzymatic systems play major roles in the antioxidant mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To protect cells from the damage caused by ROS, microorganisms have developed a variety of defense mechanisms against oxidative stress (Guan et al, ). Enzymatic systems play major roles in the antioxidant mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that reinforcing the antioxidant defense system may be a universal strategy to combat ROS generated by different target products or intermediates. Moreover, several environmental stresses also lead to oxidative stress (Guan et al, ). By using a combination of SOD and heat shock protein genetic devices, the thermotolerance and ethanol production of Saccharomyces cerevisiae were improved (Sun et al, ; K. Xu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The heat shock response has been well studied in all three domains of life, leading to the identification of several heat shock protein families . As only few members of these families were actually found to be upregulated upon continuous growth at high temperature, we systematically inspected all Haloferax proteins classified into one of the known heat shock protein families.…”
Section: Resultsmentioning
confidence: 99%
“…This confirmed that most of these are not upregulated upon continuous growth at high temperature (for full details see Text S5, Supporting Information). This is not surprising in itself as the heat shock response is rapid but transient . Among the few proteins that are strongly affected by growth temperature is the adjacently encoded gene pair HVO_O450 and HVO_O451, both members of the Hsp20‐type heat shock protein family (also known as short Heat Shock Proteins, sHSPs).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the physical and chemical properties of their environment, such as heat, cold and salt stress, oxygen and nutrient deprivation, desiccation and changes in osmolarity, threaten the survival of bacteria, and they have therefore evolved various strategies to evade detrimental effects [1][2][3].…”
Section: Introductionmentioning
confidence: 99%